Between ‘Marwah’ and Algorithm: Negotiating Digital Sexual Intimacy among Teenagers in a Minangkabau Family - Yunarti Yunarti; Siti Hanisa Khaira; Sri Meiyenti; Yulkardi Yulkardi; Jonson Handrian Ginting (Universitas Andalas, 2026)
This research examines how adolescents and families in Padang City negotiate the boundaries of intimacy, sexual expression, and surveillance in the context of an increasingly digital world. Social media is not only a space for self-expression for adolescents, but also a field of social interaction that presents tensions between traditional family values ​​and the dynamics of global digital culture. Using digital anthropology, gender studies, and participatory ethnography, this study explores the daily lives of adolescents and their families, both online and offline. The research was conducted through digital observation, in-depth interviews, and focus group discussions (FGDs) with adolescents aged 15–19 and their parents in urban and semi-urban areas of Padang City. The focus is on how social media practices—such as photo sharing, use of privacy features, and responses to sexual content—are understood, negotiated, and contested within households. The reality of adolescent digital intimacy is studied by exploring power relations, gender norms, control mechanisms, and potential conflicts and disagreements within families. This is expected to enrich anthropological understanding of changing social relations within families and communities in the information technology era. Overall, the findings suggest that digital intimacy among adolescents in Padang is best understood as a negotiated process shaped by cultural values, moral regulations, peer dynamics, and technological affordances. Adolescents are not passive recipients of digital influences, and families are not irrelevant moral institutions. Rather, both operate within a changing moral landscape where intimacy is increasingly mediated, fragmented, and context-dependent.